PENGEMBANGAN POTENSI PESERTA DIDIK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS KECERDASAN MAJEMUK (MULTIPLE INTELLIGENCE) - Muhammad Anas Ma`arif; Eka Deni Sulistyanik (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2019)
Education is one of the main roles at this time in Indonesia, especially in neutralizing human intelligence that has been created by God with many kinds of existing intelligence, it is known that Indonesian education in the curriculum aims that students with learning processes in the affective, cognitive, and psychomotor aspects, achieved well not only focus on one of them, so that the level of success is more perfect, in the perspective of Multiple Intelligence with Islamic Religious Education will be mapped how an educator can understand the intelligence of students with a variety of existing intelligence, then an educator will be prioritized for the success of the learner itself, that way when you already know how each student's intelligence, will develop the potential of the students themselves and produce an effective learning process, both Input, and Out camp will also produce well .